Aislamiento e identificación del género Cándida causantes de onicomicosis en diabéticos, hipertensos y adultos mayores usuarios del Subcentro de Motupe - Jiménez Merino, María Verónica (2022)
Onychomycosis is an infection that generally affects the toenails, representing 30% of all cutaneous fungal infections, influenced by factors such as advanced age, concomitant diseases such as diabetes and hypertension. Generally the causative agents are dermatophytes with 80% followed by yeasts with 5% to 17% and non-dermatophyte fungi with 2%. The present work aims to determine by culture the species of the Candida genus from damaged nails of diabetic, hypertensive and elderly patients users of the Motupe Subcenter, the research has a specific mixed design approach of sequential exploratory type, which, according to the purpose of the work, belongs to the derivative modality, had a total of 236 nail samples for the study. The results obtained after the analysis of the saboraud agar and potato glucose agar cultures showed that in 74 patients the result was negative, however, in 162 positive results, it was found that Trichophyton sp with 31.5% (n=51) is the most frequent cause of onychomycosis, followed by yeasts with 14.2% (n=23), by using CHROMagar™ species of Candida sp were identified and reported, being able to establish that C. glabatra has the highest frequency with 43.5% (n=10) in nail samples with onychomycosis. Through the results obtained it was possible to conclude that of the positive samples, Candida sp occupies the second place of causal agent with 14.2% (n=23), likewise that CHROMagar™ is a sensitive and specific method, since the chromogenic mixture releases compounds of different colors when degraded by specific enzymes of the yeasts. On the other hand, C.glabatra has higher frequency with 43.5 % (n=10) over the other species due to proteinases and hydrophobicity of its cell surface